Effect of creative activity on forming of spiritual - physical qualities of the personality. - Nikolaychuk I. YU; Andreeva V. V.; Lyapin V. P.; Mamaeva E. V. (Kharkov National Pedagogical University, 2010)
Process of forming of spiritual - physical qualities of the personality by remedies of use of creative activity on exercises by aerobics is construed. 120 students have taken part in conducting experiment. It is proved, that introduction in teaching and educational process of creative activity assists developing: creative fancy, friendly competition, to forming of love and mutual respect, mutual understanding, crop of traffics, sensation of pace, developing of a toughness, coordination and beauty of traffics. It is indicated, that creative self-expression of the person influences forming of a personal significance, emotional relaxedness, reliance of.